2005
DOI: 10.1529/biophysj.104.052837
|View full text |Cite
|
Sign up to set email alerts
|

Slowed N-Type Calcium Channel (CaV2.2) Deactivation by the Cyclin-Dependent Kinase Inhibitor Roscovitine

Abstract: The lack of a calcium channel agonist (e.g., BayK8644) for CaV2 channels has impeded their investigation. Roscovitine, a potent inhibitor of cyclin-dependent kinases 1, 2, and 5, has recently been reported to slow the deactivation of P/Q-type calcium channels (CaV2.1). We show that roscovitine also slows deactivation (EC(50) approximately 53 microM) of N-type calcium channels (CaV2.2) and investigate gating alterations induced by roscovitine. The onset of slowed deactivation was rapid ( approximately 2 s), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
106
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(122 citation statements)
references
References 31 publications
16
106
0
Order By: Relevance
“…The difference in Act V e between N-type and L-type channels was not correlated with any domains and thus appears to be a more distributed function. We and others have previously demonstrated that roscovitine slows deactivation of P/Q-, N-, and R-type calcium channels, which results in elevated action potential-induced calcium influx (Buraei et al 2005(Buraei et al , 2007Cho and Meriney 2006;Yan et al 2002). We show here that N-DIII is both necessary and sufficient to mediate this effect.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…The difference in Act V e between N-type and L-type channels was not correlated with any domains and thus appears to be a more distributed function. We and others have previously demonstrated that roscovitine slows deactivation of P/Q-, N-, and R-type calcium channels, which results in elevated action potential-induced calcium influx (Buraei et al 2005(Buraei et al , 2007Cho and Meriney 2006;Yan et al 2002). We show here that N-DIII is both necessary and sufficient to mediate this effect.…”
Section: Discussionsupporting
confidence: 67%
“…The tail current amplitude was plotted versus step voltage and fitted by a Boltzmann function, which yielded half-activation voltage (V 1/2 ) and slope factor. Activation and deactivation kinetics were determined with single-exponential fitting as previously described (Buraei et al 2005). Group data are calculated as means Ϯ SD throughout this report.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations